Educomunicación, estrategia para la inclusión social en niños con discapacidad en la sección básica de la Escuela de Educación Fiscal Pedro J. Menéndez Navarro de la ciudad de Guayaquil, en periodo mayo 2024 - febrero 2025. - Riera Estrada, Shirley Lorena (2025)
The research aimed to propose inclusive and adapted educommunication strategies at the Pedro J. Menéndez Navarro Public Elementary School in Guayaquil, in order to improve education and facilitate communication between students with disabilities, teachers, and families. It was based on the idea to defend that the implementation of such strategies would strengthen social inclusion. To achieve this purpose, a mixed-methods approach was applied, combining quantitative and qualitative techniques: surveys administered to teachers, non-participant direct observation in classrooms from second to seventh grade, and interviews with key actors such as the school psychologist-pedagogue, the school principal, and the CONADIS delegate. The results showed limitations in the availability of adapted educational materials and inclusive technological resources, as well as a limited use of audiovisual tools. However, teachers’ training in inclusive methodologies, the active participation of students with disabilities in school dynamics, and families’ involvement in institutional activities stood out as strengths. Hypothesis testing was carried out descriptively and analytically, confirming the importance of educommunication strategies in school inclusion. The conclusions determine that teachers adequately adapt their methodologies, students participate actively, and families are key allies for inclusion.